SKEMA PEMBIAYAAN PEMBANGUNAN INFRASTRUKTUR NON-KONVENSIONAL DI KOTA SEMARANG - Artiningsih Artiningsih; Nanda C Putri; Mohammad Muktiali; Samsul Ma'rif (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
The National government of Indonesia is trying to improve the economy and competitiveness by accelerating infrastructure development. To support this target, local governments need to provide infrastructure according to their authority as stated in UU 23/2014. However, local governments has financial limitations, so they need to be innovative and provide infrastructure efficiently. One of the innovation is utilizing a non-conventional financing. It is commonly known as non-government financing by engaging public or private sector on infrastructure development. This paper propose the non-conventional financing scheme in the city of Semarang. This research used qualitative analysis. In-depth interviews with selected agencies represented the authority of infrastructure provision purposively. It followed by Focus Group Discussion which engages the private and public agencies. Content analysis conducted to identify the need of infrastructure and existing actions which has held to overcome development financing problems. Best practices on other cities give opportunity of utilizing non-conventional financing. This research reveal with non-conventional financing scheme. It is offering the alternative of infrastructure development in the city of Semarang base on some criteria, such as economic and financial feasibilities, financing typology and capacity.